The early alphabet - Healey, John F. (London : British Museum Publications Limited, 1990)
In this generously illustrated book, John Healey outlines the basic principles of the early alphabet and describes the first attempts at alphabetic writing in the Semitic languages.
Includes index.
Keywords: Alphabet -- History; Writing -- History